Collaborative Learning in Engineering Remote Laboratories - Andrew Nafalski (2009)
This paper reports on practices in national and international on-line cooperation in engineering remote laboratories (RLs) to support student collaborative activities. A structured aid enables them, in addition to acquiring technical skills and knowledge, to develop intercultural communication skills and the global perspectives sought by their profession. The concept of a Community of Practice (CoP) is a central pedagogical consideration for collaborative learning and is discussed in the paper. After reviewing practices of others, an emphasis will be placed on a team-based laboratory environment of NetLab a remote laboratory framework created at the University of South Australia (UniSA).